Features of flipped classroom and their roles in developing the spoken English proficiency among Business English undergraduates in China - Joseph Jeyaraj, Joanna; Linlin, Zou; Ismail, Lilliati (ANI publishing, 2024)
Purpose: This study sought to investigate the characteristics of the flipped classroom model and their impact on enhancing students' proficiency in spoken English within the context of the Oral Business English course in China. Utilizing a qualitative approach, data were gathered through three research instruments: classroom observations, semi-structured interviews, and document analysis. Methodology: Data were collected from three instructors delivering Oral Business English courses and their respective students across three universities in China. These data underwent analysis through thematic analysis techniques. Findings: The results indicated that instructors employed a structured three-section class approach integrated with technological tools in their implementation of flipped classroom pedagogy. Additionally, the findings illuminated the multifaceted roles of the flipped classroom paradigm in fostering students' advancement in spoken English proficiency, encompassing the refinement of speaking abilities and the cultivation of critical thinking skills through active engagement. Despite these benefits, certain challenges were identified, including increased workload for both instructors and students, as well as occasional disruptions due to internet or technological issues. Suggestions: Moreover, the study suggested that instructors should possess a nuanced understanding of the appropriateness of activities tailored to their students' learning levels. Additionally, it emphasized the necessity for teachers to meticulously design and execute flipped classroom instruction in a systematic manner, thereby fostering heightened student engagement in speaking exercises.